Working capital management and its impact on profitability:A study listed manufacturing companies in Sri Lanka - Nimalathasan, B. (My University, 2010)
Main purpose of the study is to identify the impact of working capital management on profitability of selected listed manufacturing companies from financial year 2003-2007. Correlation and regression analysis were performed. Results reveals that cash conversion cycle (CCC) and return on assets (ROA) are negatively correlated the value of -0.127 which is highly significant at 1 percent level of significance, which means that as the cash conversion cycle increases ROA decreases. In addition inventory conversion period (ICP) is highly significant at 1 percent level. It indicates that with increasing level of ICP, ROA will be increased -0.065 levels. Further the coefficient of the CCC variable is negative at a value of -0.0503 and p value is 0.006. This implies that an increase in the number of day’s cash conversion cycle by 1 day is associated with a decline in ROA by 5.03%. The results suggest that managers can increase profitability of manufacturing firms by reducing the number of day’s inventories and accounts receivable